ANALISIS KEAMANAN DAN RISIKO INVESTASI EMAS DIGITAL TERHADAP MINAT INVESTASI: STUDI PADA PEGADAIAN DIGITAL SERVICE - Nur Iza Ripada (Kasaba, 2020)
This study aims to see: 1) investment interest in the millennial generation; 2) to look at security and digital risk; 3) the dangers of the influence and risk of digital risk that of affect investment interest in creating millennials. This research uses quantitative methods, the determination of the sample using the Slovin formula and obtained as many as 47 respondents. The data collection method uses a questionnaire conducted on millennials who have invested in gold in digital service pawnshops. The technical analysis used is multiple linear regression. The results of this study indicate that interest in investment is increasingly widespread among millennials. Women are more interested in investing than men. The security of digital gold investment is very guaranteed, while the risk of digital gold investment is that it has not been able to reach all levels of society and is still prone to fraud. And according to the ANOVA analysis results show that the Fcount value is 110.608 with a significance value of 0.000. This shows that the variables X1 and X2 simultaneously or simultaneously affect Y.